Analysis of Lay Up Shoot Movements in STKIP PGRI Bangkalan Sports Education Students - Kanza, Nabil Santia; Hidayatullah, Fajar; Widodo, Haryo Mukti; Handayani, Heni Yuli (Universitas PGRI Palembang, 2024)
Kinovea software to collect and analyze video data showing the implementation of basketball lay-up techniques by sports education students in 2022. The aim is to evaluate the level of accuracy of the movements demonstrated by the students. Before data analysis was carried out, videos were taken directly during the implementation by students. This research adopts a descriptive approach with qualitative methods. The process of taking a video using an iPhone camera. The Kinovea application is used as a tool to analyze physical conditions and body movements during lay-ups . The sample was selected using a purposive sampling method because of limited time and energy in studying a large population. It is hoped that the results of this research will provide a better understanding of the implementation of lay-up techniques and provide guidance for the development of more effective training programs in the future.